L’invention du hamac et la maison maya au Yucatán - Ramírez, Othón Baños (Anthropologica, 2022)
Facts suggest that the Maya began to adopt the Caribbean hammock in the 17th century. The Maya, however, could not absorb the hammock as a household good until they had borrowed a lengthy and complex social process that would render the hammock useful to them. This adoption and adaptation were not possible without rope manufactured from the sisal plant which originated in the Yucatan peninsula. It was also necessary that the Maya acquire the technique of weaving and that it spread. With the hammock, Maya families discovered a surprising domestic object which gave rise to formal and structural transformations of their houses.